1972
DOI: 10.1021/ja00775a046
|View full text |Cite
|
Sign up to set email alerts
|

Boat and chair transition states of 1,5-hexadiene

Abstract: CQ dication stabilizes the DNA structure by electrostatic interaction between the positive charges on CQ and the phosphate groups on DNA. In this complex the side chain of CQ is visualized as forming a bridge across the minor groove of the double helix. Since the distance across the minor groove, -10.5 A, is larger than the maximumo possible extended distance between N-2 and N-3, 7.5 A, and much larger than the distance observed in the crystal, 5.5 A, a N-2,N-3 complex across the minor groove would appear to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
42
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 0 publications
13
42
0
Order By: Relevance
“…DFT Computations of the B3LYP/6-31G* type by Houk and co-workers [23] confirmed this result. The energies for the chair-and boat-form transition states were in excellent agreement with the experimental results [24] [25]. Jiao and Schleyer [26] also attained good agreement with the experimental data by means of one-determinant method which included electron correlation (e.g., MP4SDTQ/31G*).…”
supporting
confidence: 70%
“…DFT Computations of the B3LYP/6-31G* type by Houk and co-workers [23] confirmed this result. The energies for the chair-and boat-form transition states were in excellent agreement with the experimental results [24] [25]. Jiao and Schleyer [26] also attained good agreement with the experimental data by means of one-determinant method which included electron correlation (e.g., MP4SDTQ/31G*).…”
supporting
confidence: 70%
“…It is widely accepted that chair transition states are generally preferred over the boat transition states in [3,3]-sigmatropic rearrangements. 14 Boat transition states are less common, but Ireland-Claisen transformations have been identified that preferentially proceed via boat TSs. 15 Our calculations of the protonated boat and chair transition states derived from the R - and S -hemiacetals 9 gave a strong preference for the chair transition states [by > 5 kcal/mol over the corresponding boat TSs].…”
Section: Resultsmentioning
confidence: 99%
“…The chair TS ( TS6-3 ) is still more stable, the energy difference between TS5-3 and TS6-3 is almost the same than in TS1b-2 and TS4-2 , but the energy of boat TS ( TS5-3 ) decreases to 38.0 kcal/mol, which is small enough to be overcome at 200 °C. Thus, hemiacetalization lowers the activation energy of the boat Cope TS which allows the reaction to be completed at a temperature significantly lower than the temperature that a standard boat TS would need (≈260 °C) [10]. …”
Section: Resultsmentioning
confidence: 99%
“…It is known that 1,5-dienes suffer Cope rearrangements at temperatures between 200 and 300 °C, but some structural changes in the diene, such as the anionic oxy-Cope transformation allows the reactions to happen at temperatures below 0 °C [9]. The Cope rearrangement is a [3,3]-sigmatropic reaction and in general, occurs through a single transition state (TS), which has, normally, a chair conformation due to the higher energy of the boat conformation [2,7,10–19]. In this mechanism, the electron density of the TS is delocalized into the six carbon atoms [2022].…”
Section: Introductionmentioning
confidence: 99%